2009
DOI: 10.1002/hup.1073
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of atypical antipsychotics with valproic acid. An open‐label study for most difficult patients with schizophrenia

Abstract: While these preliminary results need to be tested against tenacious monotherapy or polypharmacy involving clozapine, augmenting atypical antipsychotics with valproic acid can be useful for very severe schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 44 publications
1
28
0
Order By: Relevance
“…HDAC inhibitors are also discussed as novel targets to treat schizophrenia (15)(16)(17). In fact, valproate given in combination with atypical antipsychotics shows beneficial effects in preclinical (18) and clinical (19) studies. These data have to be interpreted with care, however, because besides its action on HDACs, valproate affects many other cellular processes (20).…”
Section: Hdac1 Links Early Life Stress To Schizophrenialike Phenotypesmentioning
confidence: 99%
“…HDAC inhibitors are also discussed as novel targets to treat schizophrenia (15)(16)(17). In fact, valproate given in combination with atypical antipsychotics shows beneficial effects in preclinical (18) and clinical (19) studies. These data have to be interpreted with care, however, because besides its action on HDACs, valproate affects many other cellular processes (20).…”
Section: Hdac1 Links Early Life Stress To Schizophrenialike Phenotypesmentioning
confidence: 99%
“…In addition, preclinical and clinical studies have found that VPA, a class I HDAC inhibitor, can augment the therapeutic effects of antipsychotics (Guidotti et al, 2009;Suzuki et al, 2009). To evaluate whether VPA can also restore the behavioral effects of HAL in aged mice, we used the CAR test and found that pretreatment with VPA restored the ability of HAL to suppress the avoidance response in aged mice and in a manner that was probably associated with the modulation of histone acetylation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to symptomatic perspectives, we believe that a 10-point change in global functioning represents a clinically pertinent one. 2 Patients in this study were fairly well controlled at baseline: their mean PANSS total score was less than 40, with good functioning as represented by a mean GAF score in the 70s. In this context, irreversibility of worsening in the intermittent treatment group is a concern.…”
mentioning
confidence: 67%